Mathematics Literature Analysis of Students of Class VIII MTs Darussalam Daun in Cooperative Learning Model Type Investigation Group - Zuhro Putri Firdausi; Marhan Taufik; Reni Dwi Susanti (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
This study aims to determine the extent of mathematical literacy skills by applying the Group Investigation type of cooperative learning model. Mathematics literacy achievement in Indonesia is still low, as seen in the PISA and TIMSS surveys, and one of the private junior high schools in Malang learning mathematics is still using conventional learning. The research method is qualitative research with a descriptive approach with nine students as the subject. The results showed that observations of teacher activities at the first meeting were 91.6% very good and the second meeting 97% very good too, observation of student activities at the first meeting 87.5% was very good and the second meeting 93.8% with very good predicates. Then the data from the student response questionnaire on the application of the GI model is an average of 4, 1, which has a good predicate. In addition, the results of the essay test to measure students' literacy skills in the application of the GI model for two meetings showed poor results at the first meeting because there were 2 students who had moderate percentage predicate, while the mathematical literacy ability of students in the second meeting was better because 7 out of 9 students with very high predicate and others with a high predicate. The data obtained based on the results of observations of teacher and student activities, student response questionnaires, and essay test results indicate that the mathematical literacy of Class VIII MTs Darussalam Daun students in the application of the Group Investigation type cooperative model has been successful and effective so that students' mathematical literacy skills are better than meeting First because most students get a very high predicate.